Kepemimpinan Islam dalam Pendidikan: Kajian Teori Perilaku dan Implementasinya - Sahmiral Amri Raja Guk Guk; Tazkiya Aulia Ibriza; Syahbudin Syahbudin; Anggun Siska Pratiwi; Nazeeva Yusrina (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore behavioral leadership theory from an Islamic perspective, particularly in the context of education. Using a descriptive qualitative approach, the research examines how Islamic values such as syura (consultation), amanah (trust), ‘adl (justice), and khalifah (stewardship) are reflected in the behavior of educational leaders in Islamic institutions. Data were collected through literature review, in-depth interviews, and participatory observation. The findings indicate that effective leadership behavior in Islamic education involves a balance between task orientation and relationship orientation, as outlined in behavioral leadership theories. Prophet Muhammad SAW is presented as the ideal leadership model who combines strategic vision with strong spiritual and moral values. These findings suggest that behavioral theory can be applied to evaluate and improve leadership styles in Islamic education that are not only professional but also grounded in Islamic principles